A change in practice after the introduction of a state-wide service plan: standardisation of the provision of care to patients with an eating disorder in a regional hospital including support from a new Eating Disorders Outreach Service. (April 2020) - Yaseen, Faisal; Bertram, Michelle; Vickery, Meg; Murphy, Michael
Objective: A state-wide service plan was introduced to guide local practice of the inpatient management of patients with an eating disorder. There was significant change in our management of such patients in our regional hospital. Our aim is to describe the changes and characterise our current practice. Method: We undertook a retrospective review of the characteristics of nine consecutive inpatients and a descriptive qualitative study to examine the care provided to the patients and to identify the resultant care provisions a year after the introduction of the service plan. Results: Patient demographics and clinical characteristics were within the expected range. By the end of the year, the following changes were identified: (i) a team of local champions emerged; (ii) a case conference and template became routine; (iii) high utilisation of the new Eating Disorder Outreach Service (EDOS); (iv) common treatment challenges and methods to address them. Conclusions: Standardisation of care and a systematic team approach are helpful in allowing small regional non-specialist centres to successfully manage complex patients. Funding of a local coordinator and assistance from EDOS was paramount to facilitate change. Other regional services may wish to adopt some of the practices described.